Doprowadź wyrażenia do najprostszej postaci i oblicz ich wartości dla podanych zmiennych:
a) (2x-3)(x+5)-2(x+1)(x+3) dla x= -3,5
b) 3(x-4)(x-1)-(2x+3)(2-x) dla x= ½

c) (3x-5)(x+2)-2(x+1)(2x-3) dla x= -1 ½

d) 3(3x-1)(4+2x)-4(x+3)(4x-1) dla x= -2 ½

2

Odpowiedzi

2010-03-03T16:48:04+01:00
A) (2x-3)(x+5)-2(x+1)(x+3) dla x= -3,5
b) 3(x-4)(x-1)-(2x+3)(2-x) dla x= ½

c) (3x-5)(x+2)-2(x+1)(2x-3) dla x= -1 ½

d) 3(3x-1)(4+2x)-4(x+3)(4x-1) dla x= -2 ½

a)2x do 2+10x-3x-15-2(x do 2 +3x+x+3)=2x do 2 +7x-15- 2x do 2-8x-6=-x-21
-3,5-21=-24,5

b)3(xdo 2-x-4x+4)-(4x-2x do 2 +6-3x)=3x do 2-15x+12-4x+2x do 2-6+3x=5xdo2-16x+6
5*1/4-8+6=5/4-2=-3/4

c)3xdo2+6x-5x-10-2(2xdo2-3x+2x-3)=3xdo2+x-10-4xdo2+2x+6=-xdo2+3x-4
9/4+9/2-4=6 i 3/4 - 4 = 2 i 3/4


d)3(12x+6xdo2-4-2x)-4(4xdo2-x+12x-3)=
30x+18xdo2 -12 -16xdo2-44x+12=-14x+2xdo2
-14*(-5/2)+2*(5/2)do 2 =70/2+2*25/4=35+50/4=35+12,5=47,5
4 2 4
Najlepsza Odpowiedź!
2010-03-03T17:36:39+01:00
A)

(2x-3)(x+5)-[2(x+1)(x+3)] = 2x^+10x-3x-15-[(2x+2)(x+3)] = 2x^+7x-15-(2x^+6x+2x+6) = 2x^+7x-15-(2x^+8x+6) = 2x^+7x-15-2x^-8x-6 = 7x-15-8x-6 = -x-21

dla x=-3,5

-(-3,5)-21 = 3,5-21 = -17,5


b)

3(x-4)(x-1)-(2x+3)(2-x) = (3x-12)(x-1)-(4x-2x^+6-3x) = 3x^-3x-12x+12-4x+2x^-6+3x = 5x^-16x+6

dla x=½

5*0,5*0,5-16*0,5+6 = 1,25-8+6 = -6,75+6 = -0,75


c)

(3x-5)(x+2)-[2(x+1)(2x-3)] = 3x^+6x-5x-10-[(2x+2)(2x-3)] = 3x^+6x-5x-10-(4x^-6x+4x-6) = 3x^+x-10-4x^+6x-4x+6 = -x^+3x-4

dla x=-1 ½

-1,5*1,5-3*1,5-4 = -2,25-4,5-4 = -6,75-4 = -10,75


d)

3(3x-1)(4+2x)-[4(x+3)(4x-1)] = (9x-3)(4+2x)-[(4x+12)(4x-1)] = 36x+18x^-12-6x-(16x^-4x+48x-12) = 18x^+30x-12-16x^-44x+12 = 2x^-14x

dla x=-2 ½

2*-2,5*-2,5-14*-2,5 = 12,5+35 = 47,5
11 4 11